Gender disparities in Albanian sports media: Analysis, challenges, and emerging transformations - Mehmeti, Elona; Orhani, Holtion (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the role of sports media in shaping public perceptions of gender representation in Albanian sports coverage. It aims to highlight the persistent disparity in the portrayal of male and female athletes and to propose strategies for promoting more equitable media narratives. Employing a qualitative research design, the study draws on a decade of relevant literature and incorporates a case study of Albanian football referee “Emanuela Rusta”. The analysis includes a review of national media coverage as well as successful international initiatives aimed at reducing gender bias in sports media. The findings reveal a pronounced gender bias in Albanian sports media. Male athletes are typically portrayed using language that emphasizes strength, competitiveness, and professionalism, while female athletes are more often described in terms of their appearance, emotions, or personal lives. The case study of “Emanuela Rusta” illustrates how female figures in sports receive disproportionate attention on non-sport-related aspects of their identity. Such framing contributes to the marginalization of women in sports discourse and limits their visibility as professional role models. The study concludes that entrenched gender stereotypes in sports media perpetuate unequal representation and hinder the progress of women in sports. It calls for comprehensive media reform and the adoption of inclusive storytelling practices to challenge these norms. The research offers practical recommendations for sports media professionals, policymakers, and advocacy groups. By adopting international best practices and promoting inclusive narratives, media outlets can play a transformative role in advancing gender equality in sports and encouraging greater female participation at all levels of athletic involvement.